2009
DOI: 10.1051/0004-6361/200912010
|View full text |Cite
|
Sign up to set email alerts
|

A submillimetre search for cold extended debris disks in the $\mathsf{\beta}$ Pictoris moving group

Abstract: Context. Previous observations with the Infrared Astronomical Satellite and the Infrared Space Observatory, and ongoing observations with Spitzer and AKARI, have led to the discovery of over 200 debris disks, based on detected mid-and far infrared excess emission, indicating warm circumstellar dust. To constrain the properties of these systems, e.g., to more accurately determine the dust mass, temperature and radial extent, follow-up observations in the submillimetre wavelength region are needed. Aims. The β P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 71 publications
8
26
0
Order By: Relevance
“…Resulting β parameters are all between 0.1 and 0.8, suggesting grains significantly larger than those in the ISM, in agreement with previous results for debris disks (e.g. Najita & Williams 2005;Nilsson et al 2009;Roccatagliata et al 2009). However, it should be noted that the presence of colder secondary dust components in addition to the fitted disk could be responsible for some abnormally low β values.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Resulting β parameters are all between 0.1 and 0.8, suggesting grains significantly larger than those in the ISM, in agreement with previous results for debris disks (e.g. Najita & Williams 2005;Nilsson et al 2009;Roccatagliata et al 2009). However, it should be noted that the presence of colder secondary dust components in addition to the fitted disk could be responsible for some abnormally low β values.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the large age uncertainties (represented by horizontal error bars) we refrain from making a fit, and instead only display dashed lines showing the expected decline for three different values of α. We conclude that the temporal evolution of the fractional dust luminosity determined from our observations is in agreement with Nilsson et al (2009), and f dust could perhaps decline as fast as the t −2 found by Spangler et al (2001), although α < 0.8 can not be excluded due to large error bars and small stellar sample. This trend will be better constrained after the completion of the ongoing APEX/LABOCA Large Programme.…”
Section: Temporal Evolution Of Debris Diskssupporting
confidence: 81%
See 2 more Smart Citations
“…6.1 for a discussion on the compatibility of the model to these observations). Therefore, the sub-mm regime is only represented by a measurement with the LABOCA bolometer array at the 12-m telescope APEX (Nilsson et al 2009, λ ∼ 870 μm), which thus represents a key piece of information. These archival data, together with our new observations, constitute the 49 measurements that are displayed in Fig.…”
Section: Spectral Energy Distributionmentioning
confidence: 99%